Expression and Transcriptional Regulation of Human ATP6V1A Gene in Gastric Cancers - Pin Wang (Nature Portfolio, 2017)
Abstract Recent studies demonstrate that the invasion and metastasis of gastric cancer (GC) is closely associated with a multi-subunit vacuolar H+-ATPase (V-ATPase). Here we investigated the expression and role of the human ATP6V1A gene that encodes the catalytic subunit A of V-ATPase in GC. We found that ATP6V1A expression level is significantly elevated in GCs compared to normals, but GC patients with higher expression levels of ATP6V1A have a better prognosis. Genomic analysis revealed that APT6V1A copy number is gained in a small fraction of GC patients and lost in a minimum number. Moreover, the ATP6V1A copy number was positively correlated with its mRNA level. To explore additional mechanisms by which ATP6V1A overexpressed in GCs, we investigated the relationship between transcription factor YY1 and ATP6V1A, and found that mRNA expression of YY1 had significant correlation with that of ATP6V1A. To validate that YY1 transcriptionally regulates ATP6V1A, we discovered that the ATP6V1A core promoter region contains three YY1 binding sites. Moreover, RNAi-mediated knockdown of YY1 in GC cells significantly decreased ATP6V1A mRNA and protein expression, while YY1 overexpression increased ATP6V1A expression level. In conclusion, YY1 may play an important regulatory role in ATP6V1A expression with potential mechanistic and clinical implications in GC.